Corporate environmentalism and brand value: A natural resource-based perspective - Rahman, Mahabubur; Rodríguez-Serrano, M. Ángeles; Faroque, Anisur R. (Journal of marketing theory and practice, 2021)
Given ever-increasing engagement of firms in corporate environmentalism over the past few decades, a multitude of studies investigated the antecedents and consequences of corporate environmentalism. Extant studies exploring the consequences of corporate environmentalism predominantly measured its effects on firm performance. However, to the best of our knowledge, no study thus far has explored whether or not the key pro-environmental initiatives pertaining to corporate environmentalism carried out by industrial firms have any effect on market-based assets, namely, brand value. This study endeavored to address this gap in the literature. Drawing on natural resource-based view of the firm (NRBV), this study argued that industrial firms committed to corporate environmentalism reap rewards in the form of higher brand value. This study investigated three salient areas of corporate environmentalism, namely, environmental innovation, efficiency in using natural resources and emission reduction. The findings of this research demonstrate that industrial firms that outperform in environmental innovation, use fewer natural resources, and reduce emission have a higher brand value. Interestingly, while environmental innovation and efficiency in using natural resources contribute fairly equally to brand value, ability to reduce emissions contributes the least to brand value creation.